2009
DOI: 10.1021/jp901859f
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Absorption Spectroscopic Study on Valence State and Local Atomic Structure of Transition Metal Oxides Doped in MgH2

Abstract: A valence state and a local structure of transition metals (Nb, V, and Ti) in MgH 2 doped with metal oxides (Nb 2 O 5 , V 2 O 5 , and TiO 2 nano ) by ball milling were examined by X-ray absorption spectroscopy (XAS). The main edge regions of the Nb, V, and Ti K-edges in the X-ray absorption near edge structure (XANES) profiles are located between 0 and +5 in the oxidation states. Since these spectra coincide with those of NbO, VO, and Ti 2 O 3 , respectively, the additives are reduced by MgH 2 to the metal ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 25 publications
1
38
1
1
Order By: Relevance
“…In order to understand the mechanistic role of Nb 2 O 5 additive, researchers have devised extensive experimental and theoretic strategies but the problem remains unsolved [20e25]. Now it is clear that, after ball milling with MgH 2 , at least a partial reduction of Nb 2 O 5 occurs [24,26,27] but little is so far known about this transformation. However, it is very clear that the existing reduced/chemically modified Nb containing species has dramatic effect to enhance the hydrogen storage performance of the remaining MgH 2 in the system.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the mechanistic role of Nb 2 O 5 additive, researchers have devised extensive experimental and theoretic strategies but the problem remains unsolved [20e25]. Now it is clear that, after ball milling with MgH 2 , at least a partial reduction of Nb 2 O 5 occurs [24,26,27] but little is so far known about this transformation. However, it is very clear that the existing reduced/chemically modified Nb containing species has dramatic effect to enhance the hydrogen storage performance of the remaining MgH 2 in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Hanada et al performed X-ray absorption spectroscopy for investigating the valences of metal oxide additives. The results showed that Nb 2 O 5 had been reduced by ball-milling with MgH 2 for 20 h. Therefore, they suggested that the improvement of desorption properties was caused by the catalytic effect of reduced niobium oxides [16]. Meanwhile, some complex compounds, such as MgNb 2 O 3.67 , have been discovered by another group [15].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they performed X-ray absorption spectroscopy for investigating the valence of metal oxide additives such as Nb 2 O 5 and V 2 O 5 . The results showed that the metal oxide had been reduced by ball-milling with MgH 2 for 20 h. Therefore, they suggested that the improvement of hydrogen sorption was caused by the catalytic effect of reduced metal oxides [13] …”
Section: Introductionmentioning
confidence: 99%